The SWIM study: Ethnic minority women's ideas and preferences for a tailored intervention to promote national cancer screening programmes-A qualitative interview study - Camilla Rahr Tatari; Berit Andersen; Trine Brogaard; Sara Badre‐Esfahani; Negin Jaafar; Pia Kirkegaard (Wiley, 2021)
Abstract Background Ethnic minority women from non‐Western countries are less likely than the native women to participate in screening programmes for cervical cancer, breast cancer and colorectal cancer. This social inequality can result in loss of possibility for prevention, delayed diagnosis and treatment and, ultimately, lower chance of survival. Developing a tailored intervention might be the solution to reduce social inequalities in cancer screening, and a key feature in intervention research is to consult the target group. Objective To explore ethnic minority women's own ideas and preferences for a cancer screening intervention and identify their attitudes to different strategies. Methods An interview study with five focus group interviews, two group interviews with an interpreter and three individual interviews. Thirty‐seven women from 10 non‐Western countries contributed to the study. The interviews were audio‐recorded and transcribed verbatim followed by a thematic analysis. Results According to the women, a tailored intervention should focus on knowledge in the form of face‐to‐face teaching. The women further suggested information material in their own language with a simple, positive and concrete communication strategy. They would like to be involved in an awareness strategy and share the knowledge with their network. Conclusion Ethnic minority women were interested in a tailored intervention, and they were keen to contribute with ideas and preferences. The findings emphasized the potential of a tailored intervention with specific suggestions to the content when attempting to reduce inequality in cancer screening participation. Patient or Public Contribution Minority women were involved in the interview study.